Responsibility and distributive justice - Knight, Carl.; Stemplowska, Zofia (Oxford : Oxford University Press, 2011)
This volume presents new essays investigating a difficult theoretical and practical problem: how do we find a place for individual responsibility in a theory of distributive justice? Does what we choose affect what we deserve? Would making justice sensitive to responsibility give people what they deserve?
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Responsibility; Distributive justice; Political science -- Philosophy